Word formation patterns in the perception domain: a typological study of cross-modal semantic associations - Norcliffe Elisabeth; Majid Asifa (Linguistic Typology)
The lexicalization of perception verbs has been of widespread interest as a route into understanding the relationship between language and cognition. A recent study finds global biases in colexification patterns, suggesting recurrent conceptual associations between sensory meanings across languages. In this paper, drawing on a balanced sample of 100 languages, we examine cross-modal semantic associations in word formation. Confirming earlier proposals, we find derived verbs are lower on a proposed Sense Modality Hierarchy (sight > hearing > touch > taste, smell) than the source perception verbs on which they are based. We propose these findings can be explained by verb frequency asymmetries and the general tendency for sources of derivations to be more frequent than their targets. Moreover, it appears certain pairings (e.g., hear–smell) are recurrently associated via word formation, but others are typologically rare. Intriguingly, the typological patterning partially diverges from the patterning reported for colexification in the same domain. We suggest that while colexification is driven by conceptual resemblance between sensory meanings, cross-modal word formations tend to arise from grammaticalization processes of lexical specification, where additional material (e.g., a sensory noun) is collocated to a polysemous verb in order to disambiguate it in context. Together, these processes can account for the typological similarities and divergences between the two phenomena. More generally, this study highlights the need to consider conceptual, communicative and diachronic factors together in the mapping between words and meanings.